(untitled) (Journal of Health, Population and Nutrition, 2012)
Little is known from developing countries about the effects of maternal morbidities diagnosed in the postpartum period on childrens development. The study aimed to document the relationships of such morbidities with care-giving practices by mothers, childrens developmental milestones and their language, mental and psychomotor development. Maternal morbidities were identified through physical examination at 6-9 weeks postpartum (n=488). Maternal care-giving practices and postnatal depression were assessed also at 6-9 weeks postpartum. Childrens milestones of development were measured at six months, and their mental (MDI) and psychomotor (PDI) development, language comprehension and expression, and quality of psychosocial stimulation at home were assessed at 12 months. Several approaches were used for identifying the relationships among different maternal morbidities, diagnosed by physicians, with childrens development. After controlling for the potential confounders, maternal anaemia diagnosed postpartum showed a small but significantly negative effect on childrens language expression while the effects on language comprehension did not reach the significance level (p=0.085). Childrens development at 12 months was related to psychosocial stimulation at home, nutritional status, education of parents, socioeconomic status, and care-giving practices of mothers at six weeks of age. Only a few mothers experienced each specific morbidity, and with the exception of anaemia, the sample-size was insufficient to make a conclusion regarding each specific morbidity. Further research with a sufficient sample-size of individual morbidities is required to determine the association of postpartum maternal morbidities with childrens development. DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11313 J HEALTH POPUL NUTR 2012 Jun;30(2):193-204